Market analysis for Rice Bran Milk: A study of consumer preference towards alternative dairy beverages in Sri Lanka - Perera, AAAHE; Gunathilake, KGT; Manawadu, TC (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Consumption of alternative dairy beverages is on the rise in many parts of the world including a developing nation like Sri Lanka. During the last few decades there has been an increase of demand for healthy plant based dairy alternatives, particularly with low fat. Hence, producing alternative dairy beverages has a great opportunity for success in the current market as it is least likely to cause allergies and is great for people with lactose intolerance. "Rice Bran Milk” is one such alternative beverage which is aimed for the people who prefer products similar to dairy beverages. For success of any product, it is necessary to forecast the market demand prior to its commercial manufacturing. Therefore, a market analysis was carried out to examine the consumer preferences of dairy beverage amongst Sri Lankans as it is believed that people who consume dairy beverages are likely to consume an alternative like Rice Bran Milk. A questionnaire survey method was used to collect primary data and random sampling method was adopted to represent the population. Data was collected from respondents representing the whole country except Northern Province. Parametric tests (one population proportion) and Non parametric tests (chi square test) were used to determine preferred product characteristics and relationship between the products attributes respectively. Product price, nutritional value, appearance of packaging, environmental impact and health benefits of the alternative dairy beverage are determined as significant drivers affecting the demand for dairy beverages. This paper investigates consumer’s preference towards dairy beverages and its implications towards dairy alternative beverages in Sri Lankan market.